The Role of Regional Languages as Markers of Cultural Identity - Wahyudi, Indra; Annisa, Anti; Nst, Siti Arafah Efendi; Manurung, Afwan Syahril (HORIZON: Indonesian Journal of Multidisciplinary, 2025)
Regional languages play a strategic role as markers of cultural identity that reflect the characteristics, values, and heritage of a community. This article examines the role of regional languages in maintaining cultural identity in the midst of modernization and globalization that tends to erode linguistic diversity. The type of research used is qualitative descriptive. The data collection technique uses interviews. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawn. The results of the data analysis found that regional languages are not only a means of communication, but also a symbol of pride and social solidarity. Regional languages contain unique expressions of traditions, customs, and life philosophies of each community group. However, social changes and the influence of national and global language dominance have led to a decrease in the use of regional languages in many regions. For this reason, efforts to preserve regional languages through formal education, cultural revitalization, and digital media are important in maintaining cultural identity in the modern era. This article emphasizes that the preservation of regional languages is an important step in maintaining cultural diversity and strengthening national identity